Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


-(-x) = x
x = x           [ since, -(-) = + ]
Therefore, LHS = RHS
Hence, verified

1 5 1
if u like this mark it as brainlest
-(-x) =x
it is very simple,
lets take a example⇒ -(-2) will be 2
that's like -(-x) =x subtraction sign will converted into addition sign...
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts